(untitled) (Australia, 2001)
The goal of an activity-directed isolation process is to isolate bioactive compounds which may provide structural leads of therapeutic importance. Whereas the traditional process of drug development is long and expensive, simple and rapid bioassays can serve as the starting point for drug discovery. This book presents a range of "bench top" bioassay techniques useful for natural product and pharmaceutical chemists involved in drug discovery and pharmacognosy. The contents detail a number of enzyme-based assays, cell-based functional bioassays and receptor radioligand binding assays along with detailed descriptions of each type. The majority of these bioassays are presented in a step-by-step format, so they could even be implemented by technical personnel with little background in microbiology, biochemistry or pharmacology.
Thử nghiệm sinh học
Keywords: Thuốc chống ung thư,Antineoplastic agents; Nghiên cứu,Phương pháp luận,Research,Methodology